Террор Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 2002)
Экземпляры: аб (20231107) / Инвентарный номер: 59713 / Цена: 60.00 / Сис.шифр: Р2 / Авт.знак: Д 71 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-445.7